Accurate stereochemistry for two related 22,26-epiminocholestene derivatives - Vega Báez, José Luis; Sandoval Ramírez, Jesús; Meza Reyes, Socorro; Montiel Smith, Sara; Gómez Calvario, Victor; Bernès, Sylvain (International Union of Crystallography, 2008)
Regioselective opening of ring E of solasodine under various conditions afforded (25R)-22,26-epiminocholesta-5,22(N)-diene-3,16-diyl diacetate (previously known as 3,16-diacetyl pseudosolasodine B), C31H47NO4, or (22S,25R)-16-hydroxy22,26-epiminocholesta-5-en-3-yl acetate (a derivative of the naturally occurring alkaloid oblonginine), C29H47NO3. In both cases, the reactions are carried out with retention of chirality at the C16, C20 and C25 stereogenic centers, which are found to be S, S and R, respectively. Although pseudosolasodine was synthesized 50 years ago, these accurate assignments clarify some controversial points about the actual stereochemistry for these alkaloids. This is of particular importance in the case of oblonginine, since this compound is currently under consideration for the treatment of aphasia arising from apoplexy; the present study defines a diastereoisomerically pure compound for pharmacological studies.